Influence of materialism and self-esteem in the relationship between social media usage and consumer propensity towards conspicuous consumption - Lee, Kar Wai (2018)
To-date, conspicuous consumptions in both developed and developing countries remains on the rise. As a developing country, there is no exception for Malaysia. The luxury goods sector in Malaysia has been growing along with the rest of the world over the past thirteen years. Current research aimed to investigate consumers’ propensity towards conspicuous consumption through examining it from the social media usage perspectives, the mediating role of materialism and moderating role of self-esteem of consumers on the relationship between social media usage and the propensity towards conspicuous consumption. The underlying theory used in the research framework is Social Comparison Theory and Veblen’s Theory of Conspicuous Consumption. The framework of this study suggests that social media platform can cause social comparison among consumers, which the comparison domains are, wealth, status and attractiveness. These comparisons can affect materialism values of consumers and leads to increasing motivation of acquisition of luxurious products and conspicuous consumption. The study also suggests that difference of high and low self-esteem is moderating the proposed relationship of social media usage and the propensity to consume conspicuously. A survey was conducted among 387 consumers using mall-intercept method at selected shopping malls to collect required data for analyses and the sample obtained consisted of Malaysian social media users aged above 18. Pearson product-moment, hierarchical multiple regression and PROCESS analyses were conducted to test the correlation between social media usage and propensity of conspicuous consumption, the mediation of materialism and moderation of self-esteem as proposed in the research framework. The result obtained indicates that social media usage has significantly influenced materialism and conspicuous consumption propensity. Materialism was found partially mediating the relationship between social media usage and propensity of conspicuous consumption; and self-esteem was found significantly moderating the relationship between social media usage and the propensity of conspicuous consumption. Overall, this study provides valuable insights on the understanding of consumers’ propensity to conspicuous consumption and related variables that are influencing it such as social media usage, materialism, and self-esteem. Consumers and authorities can benefit from these results to create awareness regarding the impact of these variables to ensure better purchase decision to be made by consumers.